Traditional Chinese medicinal herbs with bactericidal properties and their effects on the interactions of intestinal microbiota - Chua, Song-Lin (2013)
3 Traditional Chinese Medicine (TCM) formulae, namely Ya-hom powder (行军散), Ubat Po Chai Pills (保济丸) and Pil Chi-kit Teck Aun (德安风痧丸), were widely used by the East Asians in the treatment of gastrointestinal discomforts and diarrhea. However, their effects on the intestinal microbiota were not fully understood. The aim of the project was to study their effects on 3 intestinal bacteria, namely Escherichia coli, Enterrococcus faecalis and Klebsiella pneumoniae, when they are in pure culture (monoculture) and coculture). [Peer Assessment Review]